MENINGKATKAN UPAYA PENCEGAHAN PENULARAN DEMAM DENGUE MELALUI PENDIDIKAN DAN PEMBERDAYAAN MASYARAKAT DI DESA POOWO, KECAMATAN KABILA - Wulansari, Ika; Yusuf , Nur Ayun R. (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
For more than five decades, dengue fever has been a public health problem globally, not only in Indonesia. Data from Gorontalo Province in 2020 showed 954 cases of dengue fever where the morbidity and mortality rates doubled from the previous year. The high death rate due to dengue fever cannot be separated from the influence of low public knowledge, so better efforts are needed such as education and socialization regarding the prevention and treatment of dengue fever in families and communities. This community service activity aims to increase public knowledge and understanding of efforts to prevent dengue fever. After the awareness activity was carried out, it was found that public awareness about preventing dengue fever had increased and the community also participated in preventing the occurrence of dengue fever, so that the incidence of dengue fever could decrease significantly.